Performance verification and measurement uncertainty estimation for the determination of sodium chloride in butter - Moura, Thalita Cristhina de Lima; Ribeiro, Beatriz Galdino; David, Paulo Roberto Salomão; Lucena, Alex Leandro Andrade de; Andrade, Marcelo Farias de; Napoleão, Daniella Carla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The minimum parameters of identity and quality of butters in Brazil are governed by the Ministry of Agriculture, Livestock and Supply. From them it is possible to carry out the performance verification of the methodologies to guarantee the results reliability. Thus, the objective of this study was to analyze the performance of the method of determination of NaCl in butter, based on ISO 1738:2004, evaluating accuracy, precision and the limit of quantification (LOQ). The precision was obtained since the coefficients of variation found in the tests were lower than the Horwitz value. The accuracy was approved as a consequence of the confirmation of the proficiency having as provider the FAPAS. The LOQ of 0.41g of NaCl/100g of butter was established by evaluating the accuracy and the recovery in a NaCl content determination test, using a solution prepared with Certified Reference Material. To assure quality, the uncertainty associated with the NaCl measurement was also estimated, through the evaluation of the possible sources of uncertainty, among which were: weighing, analyzer, glassware and the reagent purity, with a measurement uncertainty of 0.03g NaCl/100g of sample. Finally, it was verified the conformity of the NaCl content in commercial samples according to the Brazilian legislation.